Comparison of cytoreductive partial versus radical nephrectomy in metastatic renal cell carcinoma: To be on the horns of a dilemma. Issue 2 (May 2022) - Shemshaki, Hamidreza; Al-Mamari, Said Abdallah; Al-Hooti, Qais; Geelani, Ishfaq Ahmed; Al Salmi, Issa; Narayana Kurukkal, Santosh; Kumar, Santhosh; Al Julandani, Amani; Sadeghzadeh, Samira
Background: Cytoreductive radical nephrectomy (cRN) with immunotherapy is the treatment of choice in patients with metastatic renal cell carcinoma (mRCC). Limited data are available on the role of cytoreductive partial nephrectomy (cPN) in mRCC. This study is a systematic review and meta-analysis of the evidence regarding survival rates comparing cPN versus cRN. Methods: PubMed/Medline, Scopus, Google Scholar, EMBASE, and the Cochrane Library were reviewed in December 2021 according to PRISMA. Four articles including 2669 patients were selected to enroll in the study. The identified reports were reviewed and their methodological quality was subjected to total quality assessment. The outcomes were cancer specific survival (CSS) and overall survival rate (OS). Results: Totally 2669 patients, 542 in cPN and 2127 in cRN groups enrolled in final analysis. Of the preoperative data, there were significant differences in preoperative size of tumor between cRN and cPN patients ( p  < 0.001), however Fuhrman grades were comparable between groups (low grade: p  =   0.51, high grade: p  =   0.76). There were comparable results in 1-year ( p  =   0.07), 2-year ( p  =   0.08), and 3-year ( p  =   0.71) CSS rates between cPN versus cRN. There was no significant difference between cPN versus cRN in OS rate ( p  =   0.61). Conclusion: There are comparable results between cPN and cRN in CSS and OS rate. However, due to a lack of data, future study will need to do more extensive studies using prospectively recorded patient features to evaluate the cPN and cRN in the metastatic setting.